The return of deep battle - Tchantouridze´, Lasha (Sodobni vojaški izzivi, 2025)
This study explores the reasons behind the poor operational performance of the Russian armed forces during the initial phase of the Ukraine war (2022–2023). The key finding contends that the poor performance of the regular armed forces of Russia in the Ukraine war was due to the Russian military reforms of 2008–2020. These reforms dismantled the old Soviet models of combined and joint operations and, in its place, created a model of ground warfare entirely based on light and mobile infantry battalions. The reformed forces gained a major advantage in mobility and maneuverability, but once Ukraine's defenders neutralized that advantage, the Russian units turned out to be incapable of generating successful combined arms operations. The Russian high command did find a fix to the failed operational design, and by 2023, the Russian ground forces reverted to the old Soviet operational art
Keywords: deep battle; globoka bitka; Oborožene sile; ruske vojaške reforme; Rusko-ukrajinska vojna (2014-....); Russian military reforms